Designing the ESM—Who Profits, Who Pays? - Bernhard Herz; Christian Bauer; Alexandra Hild (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
The European Stability Mechanism (ESM) is the permanent crisis prevention mechanism of the euro area. It was established in 2012 under considerable time pressure in an environment dominated by the financial crisis in the euro area. We analyze the costs of the current (suboptimal) design of the EMS and evaluate an alternative asset-backed securities (ABS) structure under different scenarios. Our simulation results indicate that switching to an ABS structure could lower EMS refunding costs by up to 2% with respect to our benchmark scenario. Moreover, the advantages of an ABS structure are found to be strongest in the mostly likely type of future crisis, namely, medium-sized requests for financial support from EMS members under economic stress accompanied by the unwillingness or inability of other EMS countries to provide new capital to the EMS.
Keywords: F34; F55; G15; 330